Households’ Decision to Participate in Cooperative Organizations: Evidence from Farmers in Akwa Ibom State, Southern Nigeria - Nsikak-Abasi A. Etim; Samuel P. Udolnyang; Elizabeth S. Ebukiba; Edet J. Udoh (Borong Newinera Publisher, 2021)
Farmer organizations are effective mechanisms for increasing agricultural production, income and reducing poverty. Regrettably, farmers have not taken advantage of the lofty benefits accruable to those who voluntarily join these organizations. The study estimated the factors influencing household’s decision to participate in cooperative organizations and also tested the level of agreement among identified constraints linked with participation. Multistage sampling procedure was employed to select 120 farmers for the study. Primary data were obtained using questionnaires. Data were analyzed using Probit model and Kendall’s coefficient of concordance. Results of analyses revealed that the mean age, years of educational attainment household size and years of farming experience were 32, 15, 5 and 7 respectively. Result of probit analysis further indicate that age of the farmer, farm income, household size, participation in meeting, major decision maker, distance of farm to the nearest road and farmers social status were the most critical factors influencing household’s decision to participate in cooperative organizations. Result of Kendall’s coefficient of concordance revealed that there was 0.42 (moderate agreement) between the ranking of constraints associated with farmers' participation in cooperative organizations. Furthermore, findings showed that the top five factors limiting households’ decision to participate in cooperative organizations were inadequate capital accumulation, high embezzlement of funds, poor leadership, recurring internal crises and lack of initiative. Policies to provide good and accessible roads, increase farmers incomes and encourage youths are rational options that will enhance effective participation in cooperative organizations.